Improvement of Qilin pills on male reproductive function in tripterygium glycoside‐induced oligoasthenospermia in rats. (14th February 2021) - Jiao, Wei; Sun, Jianling; Zhang, Xiaofei; An, Qi; Fu, Longlong; Xu, Wenbing; Xie, Hongli; Tang, Xiuming; Liu, Jianxin; Hu, Weihong; Gu, Yiqun; Zhang, Kaishu
Abstract: This study established an oligoasthenospermic rat model using tripterygium glycosides (TGs) and investigated the mechanism by which Qilin pills (QLPs) ameliorate reproductive hypofunction. Thirty‐two male Sprague Dawley rats were allocated to four equal‐sized groups: (1) the control group received continuous physiological levels of saline; (2) the oligoasthenospermia model group was induced with TGs by daily intragastric administration for 28 days; (3 and 4) oligoasthenospermic rats were treated intragastrically with low dose (1.62 g kg −1 d −1 ) and high dose (3.24 g kg −1 d −1 ) of QLPs once daily for 60 days. The QLP‐treated rats showed a marked increase ( p < .05) in testicular mass, testicular index and semen parameters compared with the untreated rats. Histopathologically, the QLP‐treated groups exhibited restored seminiferous tubules in contrast to the model group. Reactive oxygen species and malondialdehyde levels were dramatically decreased ( p < .05) in the testes of the QLP‐treated rats. QLP treatment partly reverted ( p < .05) the circulatory levels of reproductive hormones (FSH, LH, testosterone, prolactin and SHBG) and hepatic and renal function (AST, Cr and urea). Our results showed that oral QLP treatment had a curative effect on the testicular mass, sperm quality, testicular pathomorphology, antioxidants, plasmatic hormones, and liver and renal function of rats.